PEMANFAATAN MEDIA DIGITAL DALAM PENGELOLAAN KESEHATAN MENTAL REMAJA DI ERA PANDEMI - P. A. Janitra; P. Prihandini; N. Aristi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The data shows that the use of digital media is increasing, especially since the Covid-19 pandemic, especially among teenagers. In addition, various studies have also shown a link between the use of digital media and the mental health of adolescents. Thus, the ability to utilize digital media also plays an important role in managing the mental health of adolescents. This service activity aims to increase the literacy of Indonesian adolescents regarding how to use social media that is good for mental health and to educate teenagers regarding the impact of using digital media on mental health. The methods used in the implementation of this service are counseling (seminars), virtual interactive discussions, and quizzes involving teenagers, especially high school students (SMA) and university students. The results of this activity show that teenagers who become participants use digital media, especially social media, actively and participants can understand the material presented related to digital media and mental health. This can be identified through the active involvement of participants in the discussion and assessment of participants' answers in the quiz that are relevant to the material.